GE_GERICHTE P/6424/2019 vom 9. September 2019 - GE Cour de justice (2019)
EXCUSABILITÉ;QUESTION PRÉJUDICIELLE;NULLITÉ;EXPULSION(DROIT PÉNAL);NON-REFOULEMENT | CP.14; CP.17; CP.291; LEI.115.al1.letb; CPP.184; CPP.188